PEMBERDAYAAN UMKM MELALUI DIGITAL MARKETING DAN FESTIVAL BAZAR SEBAGAI TUJUAN SDG’S DESA - Zuraida Juniar Nastiti; Indah Nurmahanani (LPPM Universitas Insan Pembangunan, 2023)
The Sustainable Development Goals (SDG's) are development that prioritizes the quality of life from one generation to the next. Poverty is one of the problems in various cities in Indonesia. DKI Jakarta, as the capital city of Indonesia, still has areas that can be called KUMIS (Kumuh Miskin) in several areas, for example in the Pela Mampang Sub-district. From these problems, formed program to improve the sales quality of MSMEs in the surrounding area. Improving the quality of sales by providing counseling to MSME players about selling their products through dare and working with local youth organizations to hold bazaars around the Pela Mampang Sub-district. The bazaar activity is intended so that the community around the Pela Mampang area can participate in selling their products and can highlight existing local wisdom. The method used is Research & Development (R&D). The target audience for this program is adults aged 18-45 years. The results of this program are the implementation of socialization on the use of the marketplace as a current sales innovation and the implementation of bazaar activities as the aim of increasing the community's economy by maintaining the value of DKI Jakarta's local wisdom.